2010
DOI: 10.1016/j.neulet.2010.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of FKBP5 gene polymorphisms association with treatment response in patients with mood disorders

Abstract: The aim of our study was to assess the association between FKBP5 gene polymorphisms and treatment response in patients with mood disorders using a meta-analysis. Eight separate studies that included data from 2199 subjects were identified. Meta-analysis was performed for three FKBP5 gene polymorphisms (rs1360780, rs3800373, and rs4713916). A significant association of FKBP5 gene rs4713916 polymorphism and response rate was found in patients with mood disorders (Overall: A versus G: OR=1.28, 95%CI=1.06-1.53, P=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 65 publications
2
31
1
3
Order By: Relevance
“…Our data are consistent with those of a meta-analysis performed on patients with mood disorders, in which it was demonstrated that treatment response is associated with FKBP5 gene polymorphism rs4713916, but not with rs3800373 or rs1360780. 31 Similarly, Hawkins et al 32 demonstrated lack of association between rs3800373 and GC response in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Our data are consistent with those of a meta-analysis performed on patients with mood disorders, in which it was demonstrated that treatment response is associated with FKBP5 gene polymorphism rs4713916, but not with rs3800373 or rs1360780. 31 Similarly, Hawkins et al 32 demonstrated lack of association between rs3800373 and GC response in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 98%
“…The sensitivity of the GR to cortisol is further influenced by the FK506-binding protein 5 (FKBP5), which acts as co-chaperone of GR. FKBP5 SNPs (eg, rs1360780) have been associated with insufficient recovery of cortisol levels after psychosocial stress (Ising et al, 2008), with depression (Lekman et al, 2008;Zobel et al, 2010), and with the response to antidepressant treatment (Binder, 2009;Zou et al, 2010). Hence, these SNPs are attractive candidates to moderate the effect of prenatal maternal psychopathology on child development.…”
Section: Introductionmentioning
confidence: 99%
“…Condiciones que proveen a diario estrés moderado pero crónico, que ya ha sido identificadas como depresógenas por un grupo extenso de autores (Almeida et al, 2011;Sterner y Kalynchu, 2010;Vargas-Navarrio, Latorre-López y Parra-Cárdenas, 2011;Zou et al, 2012), ya que aumentan la reactividad, deterioran la capacidad real de respuesta y afectan la evaluación que la persona hace acerca de su capacidad.…”
Section: Discussionunclassified
“…Estar expuesto a un alto número de estresores que ocurren de forma consecutiva (con un impacto psicológico moderado), no contar con adecuado soporte familiar y estar expuesto a un ambiente familiar disfuncional, incrementan el riesgo de padecer de depresión y que esta se haga más severa, como lo muestran hallazgos similares de estudios previos realizados por Folkman (2001). Más que el impacto psicológico de un evento estresante en particular, es la acumulación de eventos de impacto psicológico moderado lo que se asocia a la aparición y agudización de la depresión en hombres (Bogdan et al, 2013;Sterner y Kalynchu, 2010;Zou et al, 2012).…”
Section: Discussionunclassified